Kamil Khalili garnered Outstanding Student Award in Academic and Intellectual Development Cluster for STEM category for the year 2019 - Siti Nurfarmy, Ibrahim (2020)
Universiti Malaysia Pahang (UMP)’s Mechanical and Automotive Engineering undergraduate Kamil Khalili Haji Abdullah’s deep interest in Science, Technology, Engineering and Mathematics (STEM) and active involvement in various STEM-related programmes earned him the Outstanding Student Award in Academic and Intellectual Development Cluster for STEM category for the year 2019.